SYNTHESIS OF 4-(4-METHOXY-PHENYL)-3-BUTENE-2-ON AND THE ACTIVITY TEST AS A FRUIT FLIES ATRACTANT - Deni Pranowo; Edhi Martono; Suputa Suputa; Muchalal Muchalal; Tutik D. Wahyuningsih; M. Yusuf Afandi (Indonesian Journal of Chemistry, 2008)
4-(4-methoxyphenyl)-3-buten-2-on has been synthesized from p-anisaldehyde and acetone via aldol condensation. The reaction was performed at room temperature under basic condition for 12 hours to give brown solid of product (m.p 64-65 oC) in 66.19 % yield. p-anisaldehyde itself was produced from oxidation of anetol major component of anise oil by the use of potassium permanganate as a oxidator. The structure of the products was analyzed by FTIR, 1H NMR and GC-MS. Activity test of 4-(4-methoxyphenyl)-3-buten-2-on as an attractant was carried out in Sleman with methyl eugenol as a reference. The result showed that 4-(4-methoxyphenyl)-3-buten-2-on was inactive compound as a fruit flies attractant and some of fruit flies, i.e. Bactrocera papayae, B. carambolae, B. umbrosa and B. abdolonginqua was found on the test area.